PENGARUH SISTEM INFORMASI AKUNTANSI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA PEGAWAI BUMDES DAN KARYAWAN JANTI PARK - Noviana Musafa’Ati; Rukmini Rukmini; Yuwita Ariessa Pravasanti (CV. Denasya Smart Publisher, 2024)
This research was conducted to determine the effect of accounting information systems, work motivation on Janti Park employee performance through job satisfaction as an intervening variable. The research method uses primary data by filling out a questionnaire. The sample data collection technique uses the Slovin technique. Data analysis methods include descriptive statistical tests, validity tests, reliability tests, classical assumption tests, normality tests, multicollinearity tests, autocorrelation tests, multiple linear regression tests, F tests, t tests, R2 tests. Partially, the influence of accounting information systems and work motivation influences employee performance. However, there is one hypothesis result that has no effect, namely the accounting information system on job satisfaction.